2009
DOI: 10.1177/193229680900300607
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Blood Glucose Monitoring in the General Surgical Population

Abstract: Several studies have shown a relationship between poor outcome and uncontrolled blood glucose (BG) in cardiac, neurosurgical, critical care, and general surgical patients. A major study showed that tight glycemic control (80–110mg/dl) was related to increased mortality. Based on evidence from controlled studies, the American Diabetes Association, and the Society of Thoracic Surgeons, maintaining intraoperative BG levels in the 140–180 mg/dl range seems appropriate. Optimization of the patient's preoperative me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 64 publications
0
21
0
2
Order By: Relevance
“…Previous results had raised concerns pertaining to their accuracy in acute care settings [81]. A recent analysis of two prospective randomized trials demonstrated both accuracy and safety of SQ continuous glucose monitoring systems in critically ill patients [82•].…”
Section: Continuous Glucose Monitoring and Closed-loop Systemsmentioning
confidence: 99%
“…Previous results had raised concerns pertaining to their accuracy in acute care settings [81]. A recent analysis of two prospective randomized trials demonstrated both accuracy and safety of SQ continuous glucose monitoring systems in critically ill patients [82•].…”
Section: Continuous Glucose Monitoring and Closed-loop Systemsmentioning
confidence: 99%
“…Hyperglycaemia and/or insulin resistance has been shown to adversely affect clinical outcomes in both diabetic and non-diabetic patients [1]. This has been confirmed for several patient categories, including pregnant women [2], patients with diabetes mellitus [3], acute myocardial infarction [4] and acute stroke [5].…”
Section: Introductionmentioning
confidence: 70%
“…This type of device might prove beneficial in a diabetic patient undergoing a long, complicated, or high-risk procedure in which frequent and accurate glucose monitoring is required. 40 As an alternative to blood sampling, subcutaneous sensors for continuous monitoring are available and have been found to correlate with BG values. These devices may not have the needed accuracy for routine use in an acute care setting such as with surgical patients.…”
Section: Diagnostic Proceduresmentioning
confidence: 99%
“…A preoperative hemoglobin A1c less than 7% confers good long-term glucose control and has been associated with decreased risk of infectious complications. 40 Continuous glucose monitoring devices can be used to obtain real-time BG analysis and allow for closer monitoring and for prevention of the deleterious effects associated with hypoglycemia. These devices can be quite accurate but require frequent calibration.…”
Section: Diagnostic Proceduresmentioning
confidence: 99%